Positive electrode active material for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery

By introducing an appropriate amount of nickel excess into the positive electrode active material of the nonaqueous electrolyte secondary battery, the Li layer structure is stabilized, and the problem of degradation of the battery charge and discharge cycle characteristics is solved, and the cycle life and overall performance of the battery are significantly improved.

JP7656806B2Active Publication Date: 2025-04-04PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023129872
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-12-26
Filing Date
2023-08-09
Publication Date
2025-04-04
Estimated Expiration
2038-12-17

AI Technical Summary

Technical Problem

The charge and discharge cycle characteristics of existing nonaqueous electrolyte secondary batteries are prone to deterioration, resulting in a degradation of battery performance.

Method used

The lithium-transfer metal oxide containing a layered structure is used as the positive electrode active material. By adjusting the nickel content and crystal structure parameters in the layered structure, the overnitine content in the Li layer is ensured to be between 1 mol% and 2.5 mol% to stabilize the Li layer structure.

Benefits of technology

It effectively suppresses the crystal structure instability caused by excessive nickel in the Li layer, extends the charge and discharge cycle life of the battery, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007656806000001
    Figure 0007656806000001
  • Figure 0007656806000002
    Figure 0007656806000002
  • Figure 0007656806000003
    Figure 0007656806000003
Patent Text Reader

Abstract

To provide a non-aqueous electrolyte secondary battery positive electrode active material capable of suppressing reduction in a charging / discharging cycle characteristic of a non-aqueous electrolyte secondary battery in the case of using lithium transition metal oxide with Ni whose ratio with respect to the total mol number of metal elements excluding Li is 91 mol% or more.SOLUTION: A non-aqueous electrolyte secondary battery positive electrode active material in one aspect of the present disclosure includes Ni-containing lithium transition metal oxide having a layered structure. The ratio of Ni in the lithium transition metal oxide is 91 mol% to 96 mol% with respect to the total mol number of metal elements excluding Li. In a Li layer of the layered structure, there exists transition metal whose ratio is 1 mol% to 2.5 mol% with respect to the total mol number of transition metal in the Ni-containing lithium transition metal oxide. The Ni-containing lithium transition metal oxide satisfies 0.30°≤n≤0.50°, where n is a half-value width of a diffraction peak of a (208) face of an X-ray diffraction pattern caused by X-ray diffraction.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a positive electrode active material for a non-aqueous electrolyte secondary battery and a technology of a non-aqueous electrolyte secondary battery.

Background Art

[0002] In recent years, as a secondary battery with high output and high energy density, a non-aqueous electrolyte secondary battery including a positive electrode, a negative electrode, and a non-aqueous electrolyte, which performs charge and discharge by moving lithium ions or the like between the positive electrode and the negative electrode, has been widely used.

[0003] As the positive electrode active material used for the positive electrode of the non-aqueous electrolyte secondary battery, for example, the following are known.

[0004] For example, Patent Document 1 discloses a positive electrode active material composed of a composite oxide represented by the composition formula Li a Ni b Co c Mn d O2 (where 0.1 ≦ a ≦ 1.2, 0.40 ≦ b < 1.15, 0 < c < 0.60, 0 < d < 0.60, and 1.00 ≦ b + c + d ≦ 1.15, 0 < c + d ≦ 0.60), and the transition metal occupancy e of the Li layer is in the range of 0.006 ≦ e ≦ 0.150.

[0005] Also, for example, Patent Document 2 discloses [Li] 3a [Ni 1-x-y Co x Al y 3b [O2] 6c (However, the subscripts in [ ] represent sites, and x and y satisfy the conditions of 0 < x ≦ 0.20 and 0 < y ≦ 0.15). In a hexagonal lithium nickel composite oxide having a layered structure, the site occupancy of metal ions other than lithium at the 3a site obtained from the Rietveld analysis of the X-ray diffraction pattern is 3% or less, and the average particle size of the primary particles is 0.1 μm or more, and the primary particles aggregate to form secondary particles. A positive electrode active material is disclosed.

Prior Art Documents

Patent Documents

[0006] [Patent Document 1] JP 2000-133262 A [Patent Document 2] JP 2000-30693 A Summary of the Invention [Problem to be solved by the invention]

[0007] In view of the above, an object of the present disclosure is to provide a positive electrode active material for a nonaqueous electrolyte secondary battery and a nonaqueous electrolyte secondary battery that are capable of suppressing deterioration in the charge-discharge cycle characteristics of the nonaqueous electrolyte secondary battery. [Means for solving the problem]

[0008] The positive electrode active material for a non-aqueous electrolyte secondary battery according to one embodiment of the present disclosure has a Ni-containing lithium transition metal oxide having a layered structure, The lithium transition metal oxide was analyzed by X-ray diffraction. The crystallinity calculated from the half-width of the diffraction peak of the (104) plane of the folded pattern using Scherrer's formula The molecular size s is in the range of 400 Å≦s≦507 Å, and the lithium transition metal oxide is The half-width n of the diffraction peak of the (208) plane in the X-ray diffraction pattern is 0.29° ≦n≦0.50° It is characterized in that:

[0009] A nonaqueous electrolyte secondary battery according to one aspect of the present disclosure is characterized by including a positive electrode having the above-described positive electrode active material for nonaqueous electrolyte secondary batteries. Effect of the Invention

[0010] According to one aspect of the present disclosure, it is possible to suppress deterioration of charge-discharge cycle characteristics. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The positive electrode active material for a non-aqueous electrolyte secondary battery according to one aspect of the present disclosure has a Ni-containing lithium transition metal oxide having a layered structure. In the Li layer of the layered structure, 1 mol% to 2.5 mol% of transition metal is present with respect to the total molar amount of the transition metal in the Ni-containing lithium transition metal oxide, and the lattice constant c indicating the c-axis length of the crystal structure obtained from the analysis result of the X-ray diffraction pattern by X-ray diffraction is in the range of 14.18 Å < c < 14.21 Å.

[0012] The layered structure of the Ni-containing lithium transition metal oxide has a transition metal layer such as Ni, a Li layer, and an oxygen layer. The charge and discharge reaction of the battery proceeds by the reversible entry and exit of Li ions present in the Li layer. Here, when the predetermined amount of transition metal is present in the Li layer of the layered structure as in the positive electrode active material for a non-aqueous electrolyte secondary battery according to one aspect of the present disclosure, even if many Li ions are extracted from the Li layer during discharge of the battery, the Li layer is retained by the predetermined amount of transition metal present in the Li layer, so it is presumed that the layered structure is stabilized and the deterioration of the charge and discharge cycle characteristics is suppressed. In the Ni-containing lithium transition metal oxide of the present disclosure, the transition metal present in the Li layer of the layered structure is mainly Ni, but transition metals other than Ni contained in the Ni-containing lithium transition metal oxide may also be present in the Li layer.

[0013] Hereinafter, an example of a non-aqueous electrolyte secondary battery using the positive electrode active material for a non-aqueous electrolyte secondary battery according to one aspect of the present disclosure will be described.

[0014] A non-aqueous electrolyte secondary battery as an example of the embodiment includes a positive electrode, a negative electrode, and a non-aqueous electrolyte. It is preferable to provide a separator between the positive electrode and the negative electrode. Specifically, it has a structure in which a wound electrode body formed by winding a positive electrode and a negative electrode via a separator and a non-aqueous electrolyte are housed in an outer package. The electrode body is not limited to a wound electrode body, and other forms of electrode bodies such as a laminated electrode body formed by laminating a positive electrode and a negative electrode via a separator may be applied. Further, the form of the non-aqueous electrolyte secondary battery is not particularly limited, and examples thereof include a cylindrical type, a square type, a coin type, a button type, and a laminate type.

[0015] The positive electrode, negative electrode, nonaqueous electrolyte, and separator used in the nonaqueous electrolyte secondary battery, which is one example of the embodiment, will be described in detail below.

[0016] <Positive electrode> The positive electrode is composed of a positive electrode current collector such as a metal foil and a positive electrode active material layer formed on the positive electrode current collector. The positive electrode current collector may be a foil of a metal such as aluminum that is stable in the potential range of the positive electrode, or a film having the metal disposed on the surface layer. The positive electrode active material layer includes, for example, a positive electrode active material, a binder, a conductive material, etc.

[0017] The positive electrode is obtained, for example, by applying a positive electrode mixture slurry containing a positive electrode active material, a binder, a conductive material, etc., onto a positive electrode current collector, drying the slurry, thereby forming a positive electrode active material layer on the positive electrode current collector, and then rolling the positive electrode active material layer.

[0018] The positive electrode active material contains a Ni-containing lithium transition metal oxide having a layered structure. The ratio of Ni to the total number of moles of metal elements other than lithium in the lithium transition metal oxide is preferably in the range of 91 mol% to 99 mol%, more preferably in the range of 91 mol% to 96 mol%, from the viewpoints of increasing the capacity of the battery and suppressing the deterioration of the charge-discharge cycle characteristics.

[0019] Examples of the layered structure of the Ni-containing lithium transition metal oxide include a layered structure belonging to the space group R-3m, a layered structure belonging to the space group C2 / m, etc. Among these, a layered structure belonging to the space group R-3m is preferred in terms of high capacity, stability of the crystal structure, etc.

[0020] The Ni-containing lithium transition metal oxide preferably contains Al in terms of suppressing the deterioration of charge-discharge cycle characteristics. For example, Al may be uniformly dispersed in the layered structure of the Ni-containing lithium transition metal oxide, or may be present in a part of the layered structure. In addition, in the manufacturing stage of the Ni-containing lithium transition metal oxide, a part of Al contained in the layered structure may precipitate on the particle surface of the Ni-containing lithium transition metal oxide, and this precipitated Al is also Al contained in the Ni-containing lithium transition metal oxide.

[0021] The Ni-containing lithium transition metal oxide may contain an element other than Al and is represented by, for example, the following general formula. Li z Ni x M 1-x-y Al y O2(1)

[0022] In the above formula, x, which indicates the proportion of Ni in the Ni-containing lithium transition metal oxide, may satisfy 0.91≦x≦0.99. However, as described above, in terms of increasing the capacity of the battery and suppressing the deterioration of the charge-discharge cycle characteristics, it is preferable that x satisfies 0.91≦x≦0.96.

[0023] In the above formula, y, which indicates the proportion of Al in the Ni-containing lithium transition metal oxide, preferably satisfies 0.04≦y≦0.09, and more preferably satisfies 0.04≦y≦0.06, in terms of suppressing deterioration of charge-discharge cycle characteristics, etc. If y is less than 0.04, the charge-discharge cycle characteristics may be deteriorated compared to when y satisfies the above range, and if y is more than 0.09, the proportion of Ni may be reduced compared to when y satisfies the above range, and the capacity of the nonaqueous electrolyte secondary battery may be reduced.

[0024] M in the above formula is not particularly limited as long as it is an element other than Li, Ni, and Al, and examples thereof include at least one element selected from Co, Mn, Fe, Mg, Ti, Cr, Cu, Sn, Zr, Nb, Mo, Ta, W, Na, K, Ba, Sr, Bi, Be, Zn, Ca, and B. Among these, in terms of suppressing a decrease in the charge-discharge cycle specificity, M in the above formula is preferably at least one element selected from Co, W, Nb, Mg, Ti, Mn, Zr, and Mo.

[0025] In the above formula, (1-xy), which represents the proportion of M in the Ni-containing lithium transition metal oxide, is 0≦(1-xy).

[0026] In the above formula, z, which indicates the ratio of Li in the Ni-containing lithium transition metal oxide, preferably satisfies 0.95≦z≦1.10, and more preferably satisfies 0.97≦z≦1.03. When z is less than 0.97, the capacity may decrease compared to when z satisfies the above range. When z is more than 1.03, more Li compound is added compared to when z satisfies the above range, which may be uneconomical from the viewpoint of production cost.

[0027] The content of elements constituting the Ni-containing lithium transition metal oxide can be measured by an inductively coupled plasma atomic emission spectrometer (ICP-AES), an electron probe microanalyzer (EPMA), an energy dispersive X-ray analyzer (EDX), or the like.

[0028] In the Ni-containing lithium transition metal oxide, the transition metal is present in the Li layer of the layered structure. The amount of the transition metal in the Li layer of the layered structure is 1 mol% to 2.5 mol%, preferably 1 mol% to 2 mol%, based on the total molar amount of the transition metal in the layered structure in order to suppress the deterioration of the charge-discharge cycle characteristics. When the amount of the transition metal in the Li layer of the layered structure is less than 1 mol%, the stability of the layered structure in a state in which the Li ions in the Li layer are extracted is reduced, and the charge-discharge cycle characteristics are reduced, compared to when the above range is satisfied. When the amount of the transition metal in the Li layer of the layered structure is more than 2.5 mol%, the diffusibility of the Li ions in the Li layer is reduced, and the battery capacity is reduced and polarization deterioration due to the increase in resistance is easily caused, compared to when the above range is satisfied. The transition metal present in the Li layer of the layered structure is mainly Ni, but is preferably Ni, Co, Mn, or the like.

[0029] The amount of transition metal in the Li layer of the layered structure can be obtained from the results of Rietveld analysis of the X-ray diffraction pattern obtained by X-ray diffraction measurement of the Ni-containing lithium transition metal oxide.

[0030] The X-ray diffraction pattern is obtained by a powder X-ray diffraction method using a powder X-ray diffractometer (manufactured by Rigaku Corporation, product name "RINT-TTR", radiation source Cu-Kα) under the following conditions. Measurement range: 15-120° Scan speed: 4° / min Analysis range: 30-120° Background; B-spline Profile function; split pseudo-Voigt function Constraint condition; Li(3a) + Ni(3a)=1 Ni(3a) + Ni(3b) = y ICSD No.;98-009-4814

[0031] In addition, the Rietveld analysis software PDXL2 (Rigaku Corporation) is used for the Rietveld analysis of the X-ray diffraction patterns.

[0032] In the Ni-containing lithium transition metal oxide, the half-width n of the diffraction peak of the (208) plane in the X-ray diffraction pattern by the X-ray diffraction is preferably 0.30°≦n≦0.50°, more preferably 0.30°≦n≦0.45°, in terms of suppressing the charge-discharge cycle characteristics. When the half-width n of the diffraction peak of the (208) plane is less than 0.30°, the Li ions in the Li layer are more strongly bound than when the above range is satisfied, and the charge-discharge cycle characteristics are deteriorated. Also, when the half-width n of the diffraction peak of the (208) plane is more than 0.50°, the crystallinity of the Ni-containing Li transition metal oxide is reduced, the skeleton of the crystal structure becomes brittle, and the crystal structure of the space group R-3m or the like cannot be maintained, resulting in a deterioration of the cycle characteristics.

[0033] The Ni-containing lithium transition metal oxide preferably has a lattice constant a indicating the length of the a-axis of the crystal structure obtained from the results of the X-ray diffraction pattern by the above X-ray diffraction in the range of 2.872 Å < a < 2.875 Å, and a lattice constant c indicating the length of the c-axis in the range of 14.18 Å < c < 14.21 Å. When the lattice constant a is 2.872 Å or less, compared with the case where the above range is satisfied, the interatomic distance in the crystal structure becomes narrow and unstable, and the charge-discharge cycle characteristics of the battery may deteriorate. Also, when the lattice constant a is 2.875 Å or more, the interatomic distance in the crystal structure becomes wide and unstable, and the output characteristics of the battery may deteriorate compared with the case where the above range is satisfied. Further, when the lattice constant c is 14.18 Å or less, the interatomic distance in the crystal structure becomes narrow and unstable, and the charge-discharge cycle characteristics of the battery may deteriorate compared with the case where the above range is satisfied. Also, when the lattice constant c is 14.21 Å or more, the interatomic distance in the crystal structure becomes wide and unstable, and the charge-discharge cycle characteristics of the battery may deteriorate compared with the case where the above range is satisfied.

[0034] The Ni-containing lithium transition metal oxide preferably has a crystallite size s calculated by the Scherrer equation from the full width at half maximum of the diffraction peak of the (104) plane of the X-ray diffraction pattern by the above X-ray diffraction in the range of 400 Å ≤ s ≤ 500 Å. When the crystallite size s of the Ni-containing lithium transition metal oxide is less than 400 Å, compared with the case where the above range is satisfied, the crystallinity decreases and the charge-discharge cycle characteristics of the battery may deteriorate. Also, when the crystallite size s of the Ni-containing lithium transition metal oxide exceeds 500 Å, compared with the case where the above range is satisfied, the diffusivity of Li deteriorates and the output characteristics of the battery may deteriorate. The Scherrer equation is represented by the following formula (2).

[0035] s = Kλ / Bcosθ (2) In formula (2), s is the crystallite size, λ is the wavelength of the X-ray, B is the full width at half maximum of the diffraction peak of the (104) plane, θ is the diffraction angle (rad), and K is the Scherrer constant. In this embodiment, K is taken as 0.9.

[0036] The content of the Ni-containing lithium transition metal oxide is preferably 90 mass % or more, and more preferably 99 mass % or more, based on the total mass of the positive electrode active material for a non-aqueous electrolyte secondary battery, from the standpoint of, for example, improving the battery capacity and effectively suppressing the deterioration of the charge-discharge cycle characteristics.

[0037] The positive electrode active material for a non-aqueous electrolyte secondary battery of this embodiment may contain other lithium transition metal oxides in addition to the Ni-containing lithium transition metal oxide. Examples of the other lithium transition metal oxides include lithium transition metal oxides having a Ni content of 0 mol % to less than 91 mol %.

[0038] An example of a method for producing a Ni-containing lithium transition metal oxide will be described.

[0039] A method for producing a Ni-containing lithium transition metal oxide includes, for example, a first step of obtaining a composite oxide containing Ni and an arbitrary metal element, a second step of mixing the composite oxide obtained in the first step with a Li compound, and a third step of firing the mixture. Each parameter, such as the amount of transition metal in the Li layer of the layered structure of the finally obtained Ni-containing lithium transition metal oxide, the half-width n of the diffraction peak of the (208) plane, the lattice constant a, the lattice constant c, and the crystallite size s, can be adjusted by, for example, controlling the mixing ratio of the raw materials in the second step and the firing temperature and time in the third step.

[0040] In the first step, for example, while stirring a solution of a metal salt containing Ni and an arbitrary metal element (Co, Al, Mn, etc.), an alkaline solution such as sodium hydroxide is dropped to adjust the pH to the alkaline side (for example, 8.5 to 11.5), thereby precipitating (co-precipitating) a composite hydroxide containing Ni and the arbitrary metal element, and the composite hydroxide is fired to obtain a composite oxide containing Ni and the arbitrary metal element. The blending ratio of Ni and the arbitrary metal element may be appropriately determined so that the ratio of Ni is in the range of 91 mol% to 99 mol%. The firing temperature is not particularly limited, but is, for example, in the range of 500°C to 600°C.

[0041] In the second step, the composite oxide obtained in the first step is mixed with a Li compound to obtain a mixture. The mixing ratio of the composite oxide obtained in the first step and the Li compound is preferably set such that the molar ratio of metal elements other than Li:Li is in the range of 1:0.98 to 1:1.15, for example, in order to facilitate adjustment of each of the above parameters to the ranges specified above. In the second step, when the composite oxide obtained in the first step is mixed with the Li compound, other metal raw materials may be added as necessary. The other metal raw materials are oxides containing metal elements other than the metal elements constituting the composite oxide obtained in the first step and Li.

[0042] In the third step, the mixture obtained in the second step is fired at a predetermined temperature for a predetermined time to obtain the Ni-containing lithium transition metal oxide according to this embodiment. The firing of the mixture in the third step is preferably performed in two stages, for example, in order to easily adjust each of the parameters to the ranges specified above. The firing temperature in the first stage is preferably in the range of, for example, 450°C to 680°C. The firing temperature in the second stage is preferably higher than the firing temperature in the first stage, and is preferably in the range of, for example, 700°C to 800°C. The firing times in the first and second stages are preferably, for example, 3 to 10 hours. The firing of the mixture obtained in the second step is preferably performed in an oxygen stream.

[0043] Regarding the firing time in the third step, the time during which the temperature exceeds the first-stage firing temperature is preferably 10 hours or less. The time during which the temperature exceeds the first-stage firing temperature includes the time from when the temperature starts to rise to the second-stage firing temperature after the first-stage firing is completed until the temperature drops below the first-stage firing temperature after the second-stage firing is completed. The difference between the first-stage firing temperature and the second-stage firing temperature is preferably 40°C or more and 300°C or less.

[0044] Other materials contained in the positive electrode active material layer will be described below.

[0045] Examples of the conductive material contained in the positive electrode active material layer include carbon powders such as carbon black, acetylene black, ketjen black, and graphite. These may be used alone or in combination of two or more.

[0046] Examples of the binder contained in the positive electrode active material layer include fluorine-based polymers, rubber-based polymers, etc. Examples of the fluorine-based polymers include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), or modified versions of these, and examples of the rubber-based polymers include ethylene-propylene-isoprene copolymers, ethylene-propylene-butadiene copolymers, etc. These may be used alone or in combination of two or more.

[0047] <Negative electrode> The negative electrode includes a negative electrode current collector such as a metal foil and a negative electrode active material layer formed on the negative electrode current collector. The negative electrode current collector may be a foil of a metal such as copper that is stable in the potential range of the negative electrode, or a film having the metal disposed on the surface layer. The negative electrode active material layer includes, for example, a negative electrode active material, a binder, a thickener, and the like.

[0048] The negative electrode is obtained, for example, by applying a negative electrode mixture slurry containing a negative electrode active material, a thickener, and a binder onto a negative electrode current collector, followed by drying to form a negative electrode active material layer on the negative electrode current collector, and then rolling the negative electrode active material layer.

[0049] The negative electrode active material contained in the negative electrode active material layer is not particularly limited as long as it is a material capable of absorbing and releasing lithium ions, and examples thereof include carbon materials, metals capable of forming an alloy with lithium, or alloy compounds containing such metals. Examples of carbon materials include graphites such as natural graphite, non-graphitizable carbon, and artificial graphite, and cokes. Examples of alloy compounds include those containing at least one metal capable of forming an alloy with lithium. Examples of elements capable of forming an alloy with lithium include silicon and tin, and silicon oxide and tin oxide, which are formed by combining these with oxygen, can also be used. In addition, a mixture of the carbon material and a compound of silicon or tin can be used. In addition to the above, a material having a charge / discharge potential with respect to metallic lithium, such as lithium titanate, higher than that of the carbon material can also be used.

[0050] The binder contained in the negative electrode active material layer may be, for example, a fluoropolymer, a rubber-based polymer, or the like, as in the case of the positive electrode, but styrene-butadiene copolymer (SBR) or a modified product thereof may also be used. The binder contained in the negative electrode active material layer may be, for example, a fluororesin, PAN, a polyimide resin, an acrylic resin, a polyolefin resin, or the like, as in the case of the positive electrode. When preparing the negative electrode mixture slurry using an aqueous solvent, it is preferable to use styrene-butadiene rubber (SBR), CMC or a salt thereof, polyacrylic acid (PAA) or a salt thereof (PAA-Na, PAA-K, or the like, or a partially neutralized salt), polyvinyl alcohol (PVA), or the like.

[0051] Examples of the thickener contained in the negative electrode active material layer include carboxymethyl cellulose (CMC), polyethylene oxide (PEO), etc. These may be used alone or in combination of two or more.

[0052] <Non-aqueous electrolyte> The non-aqueous electrolyte includes a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. The non-aqueous electrolyte is not limited to a liquid electrolyte (non-aqueous electrolyte solution), and may be a solid electrolyte using a gel-like polymer or the like. The non-aqueous solvent may be, for example, esters, ethers, nitriles such as acetonitrile, amides such as dimethylformamide, or a mixed solvent of two or more of these. The non-aqueous solvent may contain a halogen-substituted product in which at least a part of the hydrogen of these solvents is substituted with a halogen atom such as fluorine.

[0053] Examples of the esters include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate; chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, and methyl isopropyl carbonate; cyclic carboxylates such as γ-butyrolactone (GBL) and γ-valerolactone (GVL); and chain carboxylates such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), ethyl propionate, and γ-butyrolactone.

[0054] Examples of the above ethers include cyclic ethers such as 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-butylene oxide, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-cineole, crown ether, etc., and chain ethers such as 1,2-dimethoxyethane, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, ethyl vinyl ether, butyl vinyl ether, methyl phenyl ether, ethyl phenyl ether, butyl phenyl ether, pentyl phenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o-dimethoxybenzene, 1,2-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, etc.

[0055] As the above halogenated derivatives, it is preferable to use fluorinated cyclic carbonates such as fluoroethylene carbonate (FEC), fluorinated chain carbonates, fluorinated chain carboxylic acid esters such as methyl fluoropropionate (FMP), etc.

[0056] The electrolyte salt is preferably a lithium salt. Examples of lithium salts include LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiAlCl4, LiSCN, LiCF3SO3, LiCF3CO2, Li(P(C2O4)F4), LiPF 6-x (C n F 2n+1 ) x (1 < x < 6, n is 1 or 2), LiB 10 Cl 10, LiCl, LiBr, LiI, lithium chloroborane, lower aliphatic lithium carboxylates, Li2B4O7, Li(B(C2O4)F2) and other borates, LiN(SO2CF3)2, LiN(C1F 2l+1 SO2)(C m F 2m+1 SO2){l, m are integers of 0 or more} and other imide salts. The lithium salt may be used alone or in combination. Among these, LiPF6 is preferably used from the viewpoints of ion conductivity, electrochemical stability, and the like. The concentration of the lithium salt is preferably 0.8 to 1.8 mol per 1 L of the non-aqueous solvent.

[0057] <separator> The separator may be, for example, a porous sheet having ion permeability and insulation. Specific examples of the porous sheet include a microporous thin film, a woven fabric, and a nonwoven fabric. The separator may be made of an olefin resin such as polyethylene or polypropylene, or cellulose. The separator may be a laminate having a cellulose fiber layer and a thermoplastic resin fiber layer such as an olefin resin, or a separator having an aramid resin or the like applied to its surface. A filler layer containing an inorganic filler may be formed at the interface between the separator and at least one of the positive electrode and the negative electrode. Examples of the inorganic filler include oxides containing at least one of titanium (Ti), aluminum (Al), silicon (Si), and magnesium (Mg), phosphate compounds, and those whose surfaces are treated with hydroxides or the like. The filler layer may be formed by applying a slurry containing the filler to the surface of the positive electrode, the negative electrode, or the separator. EXAMPLES

[0058] The present invention will be further described below with reference to examples, but the present invention is not limited to these examples.

[0059] <Example 1> [Preparation of positive electrode active material] [Ni 0.955Al 0.045 The composite hydroxide represented by the formula ](OH)2 was calcined at 500°C for 2 hours to obtain a composite oxide containing Ni and Al (Ni 0.955 Al 0.045 LiOH and a composite oxide containing Ni and Al were mixed so that the molar ratio of Li to the total amount of Ni and Al was 0.98:1. The mixture was fired in an oxygen stream at 670°C for 5 hours, then fired at 710°C for 3 hours, and impurities were removed by washing with water to obtain a Ni-containing lithium transition metal oxide. After the first firing step was completed, the time from the start of raising the temperature to the second firing step to the time when the temperature reached the first firing step was about 4 hours. The composition of the Ni-containing lithium transition metal oxide obtained above was measured using an ICP emission spectrometer (manufactured by Thermo Fisher Scientific, product name "iCAP6300"), and the composition was found to be Li 0.97 Ni 0.955 Al 0.045 This was used as the positive electrode active material of Example 1.

[0060] <Example 2> A Ni-containing lithium transition metal oxide was produced in the same manner as in Example 1, except that LiOH and the composite oxide containing Ni and Al of Example 1 were mixed so that the molar ratio of Li to the total amount of Ni and Al was 1:1. The composition of the obtained Ni-containing lithium transition metal oxide was Li 0.98 Ni 0.955 Al 0.045 This was used as the positive electrode active material of Example 2.

[0061] <Example 3> A Ni-containing lithium transition metal oxide was prepared in the same manner as in Example 1, except that LiOH and the composite oxide containing Ni and Al of Example 1 were mixed so that the molar ratio of Li to the total amount of Ni and Al was 1.03:1. The composition of the obtained Ni-containing lithium transition metal oxide was Li 0.99 Ni 0.955 Al 0.045 This was used as the positive electrode active material of Example 3.

[0062] <Example 4> [Ni 0.955 Al 0.045 The composite hydroxide represented by the formula ](OH)2 was calcined at 500°C for 2 hours to obtain a composite oxide containing Ni and Al (Ni 0.955 Al 0.045 A Ni-containing lithium transition metal oxide was produced in the same manner as in Example 1, except that LiOH, the composite oxide containing Ni and Al, and SiO were mixed in amounts such that the molar ratio of Li to the total amount of Ni, Al, and Si was 1.05:1. The composition of the obtained Ni-containing lithium transition metal oxide was Li 0.99 Ni 0.952 Al 0.045 S 0.003 This was used as the positive electrode active material of Example 4.

[0063] <Example 5> [Ni 0.94 Co 0.015 Al 0.045 The composite hydroxide represented by the formula ](OH)2 was calcined at 500°C for 2 hours to obtain a composite oxide containing Ni, Co and Al (Ni 0.94 Co 0.015 Al 0.045 A Ni-containing lithium transition metal oxide was produced in the same manner as in Example 1, except that LiOH and the composite oxide containing Ni, Co, and Al were mixed in an amount such that the molar ratio of Li to the total amount of Ni, Co, and Al was 0.98:1. The composition of the obtained Ni-containing lithium transition metal oxide was Li 0.97 Ni 0.94 Co 0.015 Al 0.045 This was used as the positive electrode active material of Example 5.

[0064] <Example 6> A Ni-containing lithium transition metal oxide was produced in the same manner as in Example 1, except that LiOH and the composite oxide containing Ni, Co, and Al of Example 5 were mixed so that the molar ratio of Li to the total amount of Ni, Co, and Al was 1:1. The composition of the obtained Ni-containing lithium transition metal oxide was Li 0.98 Ni 0.94 Co 0.015 Al 0.045This was used as the positive electrode active material of Example 6.

[0065] <Example 7> A Ni-containing lithium transition metal oxide was produced in the same manner as in Example 1, except that LiOH and the composite oxide containing Ni, Co, and Al of Example 5 were mixed so that the molar ratio of Li to the total amount of Ni, Co, and Al was 1.03:1. The composition of the obtained Ni-containing lithium transition metal oxide was Li 0.99 Ni 0.94 Co 0.015 Al 0.045 This was used as the positive electrode active material of Example 7.

[0066] <Example 8> [Ni 0.94 Co 0.015 Al 0.045 The composite hydroxide represented by the formula ](OH)2 was calcined at 500°C for 2 hours to obtain a composite oxide containing Ni, Co and Al (Ni 0.94 Co 0.015 Al 0.045 LiOH, the composite oxide containing Ni, Co, and Al, and SiO were mixed in amounts such that the molar ratio of Li to the total amount of Ni, Co, Al, and Si was 1.05:1. Except for the above, a Ni-containing lithium transition metal oxide was produced in the same manner as in Example 1. The composition of the obtained Ni-containing lithium transition metal oxide was Li 0.98 Ni 0.937 Co 0.015 Al 0.045 S 0.003 This was used as the positive electrode active material of Example 8.

[0067] <Example 9> [Ni 0.94 Co 0.015 Al 0.045 The composite hydroxide represented by the formula ](OH)2 was calcined at 500°C for 2 hours to obtain a composite oxide containing Ni, Co and Al (Ni 0.94 Co 0.015 Al 0.045LiOH, the composite oxide containing Ni, Co, and Al, and Ti(OH)2·α-type were mixed in amounts such that the molar ratio of Li to the total amount of Ni, Co, Al, and Ti was 1.03:1. Except for the above, a Ni-containing lithium transition metal oxide was produced in the same manner as in Example 1. The composition of the obtained Ni-containing lithium transition metal oxide was Li 0.98 Ni 0.935 Co 0.015 Al 0.045 Ti 0.005 This was used as the positive electrode active material of Example 9.

[0068] <Example 10> A Ni-containing lithium transition metal oxide was prepared in the same manner as in Example 1, except that LiOH, the composite oxide containing Ni, Co, and Al of Example 9, and Ti(OH)2·α-type were mixed in amounts such that the molar ratio of Li to the total amount of Ni, Co, Al, and Ti was 1.05:1. The composition of the obtained Ni-containing lithium transition metal oxide was Li 0.98 Ni 0.935 Co 0.015 Al 0.045 Ti 0.005 This was used as the positive electrode active material of Example 10.

[0069] <Example 11> A Ni-containing lithium transition metal oxide was produced in the same manner as in Example 1, except that LiOH, the composite oxide containing Ni, Co, and Al of Example 9, and Li3MoO4 were mixed in amounts such that the molar ratio of Li to the total amount of Ni, Co, Al, and Mo was 1.075:1. The composition of the obtained Ni-containing lithium transition metal oxide was Li 0.99 Ni 0.935 Co 0.015 Al 0.045 Mo 0.005 This was used as the positive electrode active material of Example 11.

[0070] <Example 12> [Ni 0.94 Co 0.015 Al 0.045The composite hydroxide represented by the formula ](OH)2 was calcined at 500°C for 2 hours to obtain a composite oxide containing Ni, Co and Al (Ni 0.94 Co 0.015 Al 0.045 LiOH, the composite oxide containing Ni, Co, and Al, and MnO2 were mixed in amounts such that the molar ratio of Li to the total amount of Ni, Co, Al, and Mn was 1.05:1. Except for the above, a Ni-containing lithium transition metal oxide was produced in the same manner as in Example 1. The composition of the obtained Ni-containing lithium transition metal oxide was Li 0.98 Ni 0.93 Co 0.015 Al 0.045 Mn 0.01 This was used as the positive electrode active material of Example 12.

[0071] <Example 13> A Ni-containing lithium transition metal oxide was prepared in the same manner as in Example 1, except that LiOH, the composite oxide containing Ni, Co, and Al of Example 12, and MnO2 were mixed in amounts such that the molar ratio of Li to the total amount of Ni, Co, Al, and Mn was 1.08:1. The composition of the obtained Ni-containing lithium transition metal oxide was Li 0.98 Ni 0.93 Co 0.015 Al 0.045 Mn 0.01 This was used as the positive electrode active material of Example 13.

[0072] <Example 14> A Ni-containing lithium transition metal oxide was prepared in the same manner as in Example 1, except that LiOH, the composite oxide containing Ni, Co, and Al of Example 12, and LiNbO3 were mixed in amounts such that the molar ratio of Li to the total amount of Ni, Co, Al, and Nb was 1.08:1. The composition of the obtained Ni-containing lithium transition metal oxide was Li 0.99 Ni 0.93 Co 0.015 Al 0.045 Nb 0.01 This was used as the positive electrode active material of Example 14.

[0073] <Example 15> A Ni-containing lithium transition metal oxide was produced in the same manner as in Example 1, except that LiOH, the composite oxide containing Ni, Co, and Al of Example 12, and LiNbO3 were mixed in amounts such that the molar ratio of Li to the total amount of Ni, Co, Al, and Nb was 1.10:1. The composition of the obtained Ni-containing lithium transition metal oxide was Li 0.99 Ni 0.93 Co 0.015 Al 0.045 Nb 0.01 This was used as the positive electrode active material of Example 15.

[0074] <Example 16> [Ni 0.91 Co 0.045 Al 0.045 The composite hydroxide represented by the formula ](OH)2 was calcined at 500°C for 2 hours to obtain a composite oxide containing Ni, Co and Al (Ni 0.91 Co 0.045 Al 0.045 LiOH and the composite oxide containing Ni, Co, and Al were mixed in an amount such that the molar ratio of Li to the total amount of Ni, Co, and Al was 1.03:1. Except for the above, a Ni-containing lithium transition metal oxide was produced in the same manner as in Example 1. The composition of the obtained Ni-containing lithium transition metal oxide was Li 1.03 Ni 0.91 Co 0.045 Al 0.045 This was used as the positive electrode active material of Example 16.

[0075] <Example 17> A Ni-containing lithium transition metal oxide was prepared in the same manner as in Example 1, except that LiOH, the composite oxide containing Ni, Co, and Al of Example 12, and Ti(OH)2·α-type were mixed in amounts such that the molar ratio of Li to the total amount of Ni, Co, Al, and Ti was 1.10:1. The composition of the obtained Ni-containing lithium transition metal oxide was Li 0.98 Ni 0.91 Co 0.015 Al 0.045 Ti 0.03 This was used as the positive electrode active material of Example 17.

[0076] <Comparative Example 1> LiOH and NiO were mixed in amounts such that the molar ratio of Li to Ni was 1.03:1, and the mixture was fired in an oxygen stream at 670°C for 5 hours, then fired at 750°C for 3 hours, and impurities were removed by washing with water to obtain a Ni-containing lithium transition metal oxide. After the first firing stage was completed, the time from the start of raising the temperature to the second firing stage until the temperature reached the first firing stage after the second firing stage was approximately 5 hours. The composition of the Ni-containing lithium transition metal oxide obtained above was Li 0.98 Ni 1.0 This was used as the positive electrode active material of Comparative Example 1.

[0077] <Comparative Example 2> LiOH and the composite oxide containing Ni, Co, and Al of Example 5 were mixed in an amount such that the molar ratio of Li to the total amount of Ni, Co, and Al was 1.03:1. The mixture was fired in an oxygen stream at 670°C for 5 hours, and then fired at 750°C for 3 hours to obtain a Ni-containing lithium transition metal oxide. The composition of the Ni-containing lithium transition metal oxide obtained above was Li 0.98 Ni 0.94 Co 0.015 Al 0.045 This was used as the positive electrode active material of Comparative Example 2.

[0078] <Comparative Example 3> LiOH, the composite oxide containing Ni, Co, and Al of Example 12, and MnO2 were mixed in amounts such that the molar ratio of Li to the total amount of Ni, Co, Al, and Mn was 1.1:1. The mixture was fired in an oxygen stream at 670°C for 5 hours, and then fired at 800°C for 3 hours to obtain a Ni-containing lithium transition metal oxide. After the first firing stage was completed, the time from the start of raising the temperature to the second firing stage to the time when the temperature reached the first firing stage after the second firing stage was approximately 6 hours. The composition of the Ni-containing lithium transition metal oxide obtained above was Li 0.98 Ni 0.93 Co 0.015 Al 0.045 Mn 0.01 This was used as the positive electrode active material of Comparative Example 3.

[0079] < Example 18 > LiOH, the composite oxide containing Ni, Co, and Al of Example 9, and Ti(OH)2·α-type were mixed in amounts such that the molar ratio of Li to the total amount of Ni, Co, Al, and Ti was 1.1:1. The mixture was fired in an oxygen stream at 670°C for 5 hours, and then fired at 710°C for 3 hours to obtain a Ni-containing lithium transition metal oxide. The composition of the Ni-containing lithium transition metal oxide obtained above was Li 0.99 Ni 0.935 Co 0.015 Al 0.045 Ti 0.005 It was O2. Example 18 The positive electrode active material was

[0080] < Example 19 > LiOH and the composite oxide containing Ni, Co, and Al of Example 5 were mixed in an amount such that the molar ratio of Li to the total amount of Ni, Co, and Al was 1.05:1. The mixture was fired in an oxygen stream at 670°C for 5 hours, and then fired at 710°C for 3 hours to obtain a Ni-containing lithium transition metal oxide. The composition of the Ni-containing lithium transition metal oxide obtained above was Li 0.98 Ni 0.94 Co 0.015 Al 0.045 It was O2. Example 19 The positive electrode active material was

[0081] < Comparative Example 6 > [Ni 0.88 Co 0.09 Al 0.03 The composite hydroxide represented by the formula ](OH)2 was calcined at 500°C for 2 hours to obtain a composite oxide containing Ni, Co and Al (Ni 0.88 Co 0.09 Al 0.03LiOH and the composite oxide containing Ni, Co and Al were mixed in amounts such that the molar ratio of Li to the total amount of Ni, Co and Al was 1.03:1. The mixture was fired in an oxygen stream at 670°C for 5 hours, then fired at 750°C for 3 hours, and impurities were removed by washing with water to obtain a Ni-containing lithium transition metal oxide. After the first firing stage was completed, the time from the start of raising the temperature to the second firing stage to the time when the temperature reached the first firing stage after the second firing stage was approximately 5 hours. The composition of the Ni-containing lithium transition metal oxide obtained above was Li 0.98 Ni 0.88 Co 0.09 Al 0.03 It was O2. Comparative Example 6 The positive electrode active material was

[0082] <Comparative Example 7> LiOH and Comparative Example 6 The composite oxide containing Ni, Co and Al was mixed in an amount such that the molar ratio of Li to the total amount of Ni, Co and Al was 1.05:1. Comparative Example 6 The composition of the Ni-containing lithium transition metal oxide obtained above was Li 0.99 Ni 0.88 Co 0.09 Al 0.03 This was used as the positive electrode active material of Comparative Example 7.

[0083] Example 1 19 and Comparative Example 1 3、6~8 Powder X-ray diffraction measurements were performed on the Ni-containing lithium transition metal oxide (positive electrode active material) under the conditions described above to obtain X-ray diffraction patterns. Diffraction lines indicating a layered structure were confirmed in all of the X-ray diffraction patterns of the examples and comparative examples.

[0084] From the X-ray diffraction patterns of each Example and Comparative Example, the transition metal amount in the Li layer, the half-width of the diffraction peak of the (208) plane, the lattice constant a, the lattice constant c, and the crystallite size s were determined. The results are summarized in Tables 1 and 2. The measurement methods are as described above.

[0085] [Table 1]

[0086] [Table 2]

[0087] Example 1 19 and Comparative Example 1 3、6~8 A test cell was prepared as follows using the above Ni-containing lithium composite oxide (positive electrode active material).

[0088] [Preparation of positive electrode] The positive electrode active material of Example 1 was mixed in a ratio of 91 parts by mass, 7 parts by mass of acetylene black as a conductive material, and 2 parts by mass of polyvinylidene fluoride as a binder. The mixture was kneaded using a kneader (TK Hibismix, manufactured by Primix Corporation) to prepare a positive electrode mixture slurry. Next, the positive electrode mixture slurry was applied to an aluminum foil having a thickness of 15 μm, and the coating was dried to form a positive electrode active material layer on the aluminum foil. This was the positive electrode of Example 1. Positive electrodes were prepared in the same manner in the other Examples and Comparative Examples.

[0089] [Preparation of non-aqueous electrolyte] Ethylene carbonate (EC), methyl ethyl carbonate (MEC), and dimethyl carbonate (DMC) were mixed in a volume ratio of 3:3:4. Lithium hexafluorophosphate (LiPF6) was dissolved in the mixed solvent to a concentration of 1.2 mol / L to prepare a non-aqueous electrolyte.

[0090] [Preparation of test cell] The positive electrode of Example 1 and the negative electrode made of lithium metal foil were laminated so as to face each other with a separator interposed therebetween, and the laminate was wound to prepare an electrode body. Next, the electrode body and the non-aqueous electrolyte were inserted into an aluminum exterior body to prepare a test cell. Test cells were prepared in the same manner in the other Examples and Comparative Examples.

[0091] [Measurement of capacity retention rate during charge / discharge cycle characteristics] At an environmental temperature of 25° C., the test cells of each Example and Comparative Example were charged at a constant current of 0.2 C until the battery voltage reached 4.3 V, then charged at a constant voltage of 4.3 V until the current value reached 0.05 mA, and discharged at a constant current of 0.2 C until the battery voltage reached 2.5 V. This charge / discharge cycle was repeated 20 times, and the capacity retention rate in the charge / discharge cycle of the test cells of each Example and Comparative Example was calculated by the following formula. The higher this value, the more suppressed the deterioration of the charge / discharge cycle characteristics. Capacity retention rate = (discharge capacity at 20th cycle / discharge capacity at 1st cycle) x 100

[0092] Tables 3 and 4 show the results of the capacity retention rate in the charge-discharge cycles of the test cells of each of the Examples and Comparative Examples.

[0093] [Table 3]

[0094] [Table 4]

[0095] Examples 1 to 17 and Comparative Examples 1 to 3 All of the positive electrode active materials have a Ni-containing lithium transition metal oxide having a layered structure, and the ratio of Ni in the lithium transition metal oxide is 91 mol % or more with respect to the total number of moles of metal elements excluding Li. Among these, Examples 1 to 17 have a Ni ratio of 91 mol % to 99 mol %, the Li layer of the layered structure has a transition metal of 1 to 2.5 mol % with respect to the total molar amount of transition metal in the Ni-containing lithium transition metal oxide (i.e., the transition metal amount in the Li layer is 1 to 2.5 mol %) with respect to the total molar amount of transition metal in the Ni-containing lithium transition metal oxide, and the half-width n of the diffraction peak of the (208) plane in the X-ray diffraction pattern by X-ray diffraction of the lithium transition metal oxide is 0.30°≦n≦0.50°, whereas Comparative Examples 1 to 17 have a Ni ratio, a transition metal amount in the Li layer, and a half-width n of the diffraction peak of the (208) plane that do not satisfy the above range. 3Compared to the previous example, the capacity retention rate was higher and the deterioration of the charge-discharge cycle characteristics was suppressed. 。

Claims

1. The present invention has a layered structure of a Ni-containing lithium transition metal oxide, the Li layer of the layered structure contains 0.8 mol % to 2.5 mol % of transition metal relative to the total molar amount of transition metal in the Ni-containing lithium transition metal oxide; The lithium transition metal oxide has a crystallite size s in the range of 400 Å≦s≦507 Å, calculated from the half-width of the diffraction peak of the (104) plane in an X-ray diffraction pattern by Scherrer's formula; The lithium transition metal oxide has an X-ray diffraction pattern in which the half-width n of a diffraction peak of a (208) plane satisfies the range of 0.29°≦n≦0.50°.

2. 2. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the lithium transition metal oxide contains at least one selected from the group consisting of Co, W, Nb, Mg, Ti, Mn, Zr and Mo.

3. 3. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the lithium transition metal oxide contains Al.

4. 4. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the Li layer of the layered structure contains at least one selected from the group consisting of Ni, Co and Mn.

5. A non-aqueous electrolyte secondary battery comprising a positive electrode containing the positive electrode active material for non-aqueous electrolyte secondary batteries according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Nonaqueous secondary battery

    JP1997298061A

  • Positive electrode active material for lithium battery, its manufacture, and lithium battery using it

    JP1998321228A

  • Positive electrode active material for nonaqueous electrolyte secondary battery and its manufacture

    JP2000030693A

  • Nonaqueous electrolyte secondary battery

    JP2000133262A

  • Non-aqueous electrolyte rechargeable battery

    JP2004127675A